Why East Asia overtook Latin America : agrarian reform, industrialisation and development - Kay, Cristóbal (2002)
Focuses mainly on three interconnected factors in seeking to understand why the East Asian newly industrialising countries outperformed Latin America i.e. firstly state capacity and policy performance; secondly character of agarian reform and its impact on equity and growth; thirdly interactions between agriculture and industry in development strategies.